Beauveria bassiana, Bb11, to control the Diamondback moth, Plutella xylostella (L.) (Lepidoptera: Plutellidae) on cabbage in Ghana - Osae, Michael; Marri, Dinah (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
An operational scale, efficacy tests of the optimal dose of the bioinsecticide Bb11 (Bba5653), including observation data on useful non-targets. Specifically, participatory trials with vegetable growers were carried out, at the Tuba Irrigation Site in the Ga West District of the Greater Accra Region of Ghana, to demonstrate the effectiveness of the biological insecticide Bba5653 under field conditions in Ghana. The demonstration also included the evaluation of BSF frass in cabbage production systems. The impact of BSF frass on plant growth, pest and disease tolerance and yield was demonstrated.The Bb11 biopesticide was able to control the DBM to the satisfaction of the farmers and partners. However, the presence of high aphid infestation was a challenge as the Bb11 biopesticide was not able to control the Aphids. Emastar outperformed all the Bb11 as an insecticide treatment in terms of pest infestation and yield. This is because Emastar was effective against all the different types of pests present on the field. The effects of BSF frass, mainly on crop yield and other parameters was not obvious because of the high aphid infestation which resulted in widespread viral diseases and stunting on the control and Bb11 treated plots. To draw conclusions, it is important to repeat the trial taking into consideration the aphid situation and put in place measures to integrate other tools that can deal with the aphids and other pests that are not amenable to control by Bb11.